: ; Multiple missions in the midst of war: Integrating Ukraine's recovery and EU Accession - Julian Bergmann; Miriam Kosmehl; Julia Langbein; Gwendolyn Sasse (German Institute of Development and Sustainability (IDOS), 2024)
: , , . , , , . , . , Ukraine Facility 2027 , . . , , , . c , : - , . , , . « » , , , . - . , (URC) 2024 , , URC . , URC. - , ., - G7, , . - . - . , , (, , , ) , , , . He , . - . - , . - . , , . .
Keywords: 320; Ukraine; Ukraine-EU relations; recovery; reconstruction; EU accession; EU enlargement policy